OPTIMALISASI PENGEMBANGAN RUMAH BIBIT PADA KELOMPOK WANITA TANI REZEKI BERSAMA DI KELURAHAN BERINGIN RAYA KOTA BENGKULU - Welly Herman; Teguh Adiprasetyo; Bandi Hermawan (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Seedling house is a very important thing to support plant propagation in order to realize the Sustainable Food House Area (KRPL) program. Through this service activity, the service team tries to develop a simple nursery to support the program. The objectives of this activity are (1) to determine the potential for developing a nursery to create a sustainable food house area in the Beringin Raya Village, Bengkulu City and (2) to increase the ability of the Women Farmers Group (KWT) Sustenance Bersama in managing and developing seedling houses. The method used is a PRA (Participatory Rural Appraisal) approach which is implemented through outreach activities and direct practice in the field. The results of this service activity are fostering the spirit of KWT members in optimizing the use of seed houses that have been developed by the service team and increasing community understanding and skills in utilizing seed houses through nurseries of various types of plants.